EFFECT OF BETEL LEAF EXTRACT (Piper betle L.) ON Aeromonas hydrophila DISEASES IN TILAPIA (Oreochromis niloticus) SEED - Ahmad Zaeroni; Dewi Nuraini Setyowati; Fariq Azhar (Aquaculture Department, University of Mataram, 2022)
Seed is essential in aquaculture activities, but tilapia hatcheries often suffer from disease attacks caused by Aeromonas hydrophila bacteria, causing losses for hatchery businesses. One of the natural ingredients for treating Aeromonas hydrophila is betel leaf extract. This study aims to analyze the effect of betel leaf extract (Piper betle L.) on Aeromonas disease hydrophila on fish fry tilapia (Piper betle L.). This study used a completely randomized design (CRD) with 5 treatments and 3 replications. The treatment used was a dose of betel leaf extract (P1) 0.4 ml, (P2) 0.6 ml, (P3) 0.8 ml, (P4) positive control, (P5) negative control. The parameters observed were survival rate, specific growth rate, feed conversion ratio, absolute length growth, erythrocytes, hemoglobin, hematocrit, leukocytes, differential leukocytes, total bacteria count, and water quality. The results of this study showed that before and after the challenge test, the best average values were P3 leukocytes (1.06 and 1.4 x 10 5 ), erythrocytes (0.90 and 0.93 x 10 5 ), hemoglobin (10.9 and 9.7), hematocrit (10.7 and 10.3), total bacteria (7 x 10 1 ). Then the worst value on P1 leukocytes (0.74 and 0.87 x 10 5), erythrocytes (0.86 and 0.75 x 10 5 ), hemoglobin (10.7 and 7.7), hematocrit (10.3 and 9.3), total bacteria (74 x 10 2 ). The study concluded that the best treatment was found in treatment 3 with a dose of 0.8 ml of betel leaf extract, which significantly increased the immune system in tilapia seeds.